(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
Calcareous nannofossil assemblages have been investigated by means of quantitative analyses in three Oligocene pelagic sections located in the Umbria-Marche Apennines (Central Italy). The studied sections mainly consist of marly limestones and marls belonging to the Scaglia Cinerea Formation, and include the interval between NP23 and NP25 representing a time interval of about 3.5 Ma. Biostratigraphic resolution is extremely low and only two standard bioevents are known, which are the FO of Sphenolithus ciperoensis and the LO of Sphenolithus distentus. The distribution patterns of poorly known or recently described calcareous nannofossils provided a valuable tool for improving the current biostratigraphic framework. The studied interval is characterized by significant changes in the calcareous nannofossil assemblages and by several extinction events. The last occurrence (LO) and/or the last common occurrence (LCO) here proposed are: the LO of Sphenolithus akropodus, the LO of Reticulofenestra circus, the LCO of Helicosphaera ethologa, the LCO of Helicosphaera compactathe LO of Discoaster tanii nodifer. The reversal in abundance between Sphenolithus predistentus and S. distentus provided an additional biostratigraphic constraint at the NP23-NP24 transition. In addition biometric criteria enabled the recognition of the first common occurrence (FCO) of Cyclicargolithus abisectus > 12 mm as potential bioevent within NP24. The quantitative distribution of Sphenolithus distentus suggests to rely on the LCO of the species rather than on the LO, for the identification of NP24-NP25 boundary. The identified bioevents is a first step towards the improvement of the present Mediterranean biostratigraphic framework of the Oligocene geological record. A preliminary correlation of the bioevents to the Geomagnetic Polarity Time Scale is presented.